1994
DOI: 10.1002/eji.1830241008
|View full text |Cite
|
Sign up to set email alerts
|

B and T lymphocyte subsets enter peripheral lymph nodes and Peyer's patches without preference in vivo: no correlation occurs between their localization in different types of high endothelial venules and the expression of CD44, VLA‐4, LFA‐1, ICAM‐1, CD2 or L‐selectin

Abstract: Many lymphocytes enter tissues such as peripheral lymph nodes, and Peyer's patches through high endothelial venules (HEV). It is known that HEV differ in the expression of adhesion molecules as lymphocyte subsets do. Through the interaction of these molecules B and T lymphocyte subsets are thought to be preferentially directed into lymphoid organs. However, it is unclear which role these mechanisms play in vivo, since there are no studies demonstrating that blood lymphocyte subsets preferentially interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 30 publications
(16 reference statements)
0
18
0
Order By: Relevance
“…The affinity of adhesion molecules for their ligands can be modulated by activation, accompanied by a conformational change [4]. Therefore, the homing of lymphocytes to particular tissues cannot be predicted solely on the basis of differential integrin expression [5].…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of adhesion molecules for their ligands can be modulated by activation, accompanied by a conformational change [4]. Therefore, the homing of lymphocytes to particular tissues cannot be predicted solely on the basis of differential integrin expression [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to Dustin et al [1986] ICAM-1 is expressed in germinal center cells including B cells in vivo. In a recent study a much higher ICAM-1 expression was documented on rat B lymphocytes than T cells [Westermann et al, 1994]. Simple criteria to differentiate T and B lymphocytes with scanning electron microscopy depend on the development of microvilli; B cells have a lot of microvilli [Lin et al, 1973;Polliack et al, 1974].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in rats by Pabst, Westermann, and others [122, 123], who used unseparated cell populations and identified each subset immunohistologically subsequent to the migration, showed that both T and B cells enter various LNs with similar kinetics and in similar numbers, although T cells express L-selectin more abundantly than do B cells in rats [122]. Given these observations, they suggested that if B cells recirculate more slowly than T cells, it might be due to the difference in the retention time of B and T cells in lymphoid tissues rather than to the efficiency of their entry [122, 123]. …”
Section: Remaining Enigmasmentioning
confidence: 99%